PRAGMATIC ALTERNATIVE CONSTRUCTION (FRONTING, LEFT DISLOCATION, AND TOPICALIZATION) IN LAMALERA DIALECT - yosef - demon (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract Left dislocation construction, fronting construction and topicalization construction are universal linguistic alternations. Nevertheless these three constructions have characteristics that are very different from one language to another. This distinction depends on the language system of every language. This research data is obtained from the result of conversation between speakers of Lamaholot dialect of Lamalera. The result of data analysis proves that LDLL has three alternative constructions. The use of real language in everyday communication, this alternative construction ear has a gradative usage frequency. Left dislocation construction has the lowest usage frequency while the construction of precision and topicalization construction is significant. However, the construction of forging and parsing differed from one to another. Left dislocation construction is the advancement of peripheral arguments while topicalization construction is the construction of core argument prediction. The construction of topicalization is a passive-like construction (derivative construction). Keywords: Left dislocation construction, fronting construction and topicalization construction